2004
DOI: 10.1021/ja046858w
|View full text |Cite
|
Sign up to set email alerts
|

Helical Aromatic Oligoamides:  Reliable, Readily Predictable Folding from the Combination of Rigidified Structural Motifs

Abstract: Factors responsible for the folding of aromatic oligoamides with backbones rigidified by local three-center H-bonds were investigated. The stability of the three-center H-bonds was quantified by the half-lives of amide proton-deuterium exchange reactions, which show that the three-center H-bonds were largely intact at room temperature in the oligomer examined. This result is consistent with our current and previous 2D NMR studies. The overall helical conformation of nonamer 1 was found by variable-temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
73
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 120 publications
(78 citation statements)
references
References 85 publications
3
73
0
2
Order By: Relevance
“…[15,17] We have recently demonstrated that rationally designed hydrogenbonded foldamers from aromatic oligoamides represent versatile self-assembling scaffolds [18] and acyclic receptors for the recognition of discrete guests. [19] Herein, we describe that 1) strong interactions are generated between F···H À N hydrogen-bonding-induced foldamers and fullerenes (C 60 and C 70 ), and 2) that these interactions may be utilized for the construction of structurally unique supramolecular nano networks.…”
Section: Introductionmentioning
confidence: 99%
“…[15,17] We have recently demonstrated that rationally designed hydrogenbonded foldamers from aromatic oligoamides represent versatile self-assembling scaffolds [18] and acyclic receptors for the recognition of discrete guests. [19] Herein, we describe that 1) strong interactions are generated between F···H À N hydrogen-bonding-induced foldamers and fullerenes (C 60 and C 70 ), and 2) that these interactions may be utilized for the construction of structurally unique supramolecular nano networks.…”
Section: Introductionmentioning
confidence: 99%
“…14 More recently, conformational and configurational pre-organization in macrocyclization has been studied, e.g. folding of oligoamides, 15 synthesis of cycloparaphenylens, 16 and peptidomimetic macrocycles. 17 In order to address the dearth of novel macrocyclic scaffolds for screening campaigns, we have undertaken a research program aimed at developing methods for facile synthesis of macrocycles from simple precursors.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the one-step condensation reaction of monomeric diamines and diacid chlorides was found to lead to the highly efficient formation of a series of shape-persistent cyclized oligoamide products in yield of 60-80% [10]. Different from ordinary cyclic aromatic oligoamides that are often associated with flexible amide bonds, these macrocycles are backbone rigidified by intramolecular hydrogen bonds with few degrees of conformation freedom, and thus have well-defined cavities containing introverted O atoms [11].…”
Section: Introductionmentioning
confidence: 99%